A Study on Online Learning Environment during COVID-19 - Gargi Gohel (AG Volumes, 2022)
Global educational institutions are presently using online learning environments to give students with continual instruction throughout the pandemic of the COVID-19. Even while research on online learning has made achievements in exposing student experiences in various settings (such as university, adult, and professional education), very little progress has been made in understanding the experience of the student population, especially when the emphasis is confined to separate school years (i.e., primary and secondary school students). As a consequence of the COVID-19 epidemic, we’ve all had to make considerable changes to our daily routines. Numerous University students who had been enrolled in on-campus classes in the past now find themselves in unforeseen online learning because businesses have migrated to remote work whenever it is viable to do so. Educational institutions have been forced to adopt distant learning. Even though the online learning environment has a lot of beneficial features that make it the option that millions of students would choose if given the choice, it is not without its challenges, particularly for students who are more accustomed to attending classes in the conventional setting of a classroom.